2020
DOI: 10.22402/j.rdipycs.unam.6.2.2020.282.372-387
|View full text |Cite
|
Sign up to set email alerts
|

Incremento en la entrega de tareas escolares por medio de la economía de fichas grupal

Abstract: En este trabajo se buscó incrementar la entrega de tareas escolares en un grupo de alumnos de sexto grado de primaria de una escuela privada, con edades entre los 11 y 12 años, en la asignatura de inglés. Para lo anterior, se usó una economía de fichas grupal en el que se usaron reforzadores positivos que eligieron los propios alumnos y el costo de respuesta por el incumplimiento en la entrega o entrega incompleta de las tareas solicitadas; se establecieron 80 tareas grupales como mínimo para el acceso a los r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…The results demonstrated that a significant percentage of students do not comply with their schoolwork and that this is a strategy frequently used by teachers, designed with characteristics such as: didactic elaboration, simplicity and clarity, with benefits in meaningful learning and the review of contents. Schoolwork is specially assigned for its development at home (Amador-Salinas et al, 2020); it is an inevitable part of student life, so it must be a pleasant activity that promotes learning (Varela et al, 2021). They usually vary in quantity and difficulty, their development impacts performance because they are assigned an evaluation index (Amador-Salinas et al, 2020), they must be connected to the learning objectives of each educational stage and be presented in a volume acceptable to students.…”
Section: Graph 2 Observation Of Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated that a significant percentage of students do not comply with their schoolwork and that this is a strategy frequently used by teachers, designed with characteristics such as: didactic elaboration, simplicity and clarity, with benefits in meaningful learning and the review of contents. Schoolwork is specially assigned for its development at home (Amador-Salinas et al, 2020); it is an inevitable part of student life, so it must be a pleasant activity that promotes learning (Varela et al, 2021). They usually vary in quantity and difficulty, their development impacts performance because they are assigned an evaluation index (Amador-Salinas et al, 2020), they must be connected to the learning objectives of each educational stage and be presented in a volume acceptable to students.…”
Section: Graph 2 Observation Of Studentsmentioning
confidence: 99%
“…Therefore, it is considered essential to increase the preparation and delivery of homework through activities that also improve the relationship between students and their parents, especially in the subjects of mathematics, reading and writing (Amador-Salinas et al, 2020). Teachers can use strategies in planning homework that helps strengthen meaningful learning and empower students in preparing homework, which can include activities to connect with prior knowledge before including a topic, teaching key concepts, and help find the logic behind the information, activities focused on discussion and collaboration among others.…”
Section: Graph 2 Observation Of Studentsmentioning
confidence: 99%
“…Asimismo, se puede concluir que las familias de estudiantes de Educación Secundaria perciben un volumen de deberes individuales, grupales y digitales mayor que aquellas que tienen a sus hijos en Educación Infantil o Primaria. En consonancia, durante el confinamiento se incrementaron los niveles de autonomía en la realización de los deberes de forma individualizada, especialmente en Educación Secundaria (Hernández-Prados y Gil-Noguera, 2022; Ribeiro et al, 2021), donde también se inician de forma más intensa en los trabajos grupales (Amador-Salinas et al, 2020). Sin embargo, este tipo de tareas escolares ha sido una de las más damnificadas por la pandemia, reduciéndose considerablemente en todos los niveles educativos, aunque de manera drástica en la etapa de Infantil, en la que estas dinámicas grupales se asocian generalmente al juego y al ocio, e implican un contacto directo con los otros (Varela et al, 2021).…”
Section: Discusión Y Conclusionesunclassified
“…Por otra parte, la realización de tareas escolares individuales, ante la incursión de un nuevo modelo educativo en el que la cooperación se define como un principio prioritario, estaba viéndose compensada con tareas grupales (Erbil, 2020), que contribuían a incrementar el compromiso del alumnado, el sentimiento de responsabilidad y el éxito en su realización (Amador-Salinas et al, 2020). Sin embargo, la pandemia ha supuesto un retroceso al respecto, puesto que ha impedido los encuentros presenciales.…”
Section: Introductionunclassified